Eksplorasi Sejarah Melalui Outdoor Learning: Pembelajaran Sejarah Mahasiswa di Situs Megalitikum Pokekea, Kabupaten Poso: Exploring History Through Outdoor Learning: History Learning for Students at the Pokekea Megalithic Site, Poso Regency. - Nur, Rizka Fadliah (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
This research aims to examine the outdoor learning approach at the Pokekea Megalithic Site in increasing historical understanding among Tadris Social Sciences (TIPS) students at UIN Datokarama Palu. This approach allows students to learn directly on site, develop observation skills, and explore local cultural values ​​and history. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The research results show that learning at megalithic sites can increase student enthusiasm and participation, deepen their understanding of historical concepts, and strengthen appreciation of local cultural heritage. Therefore, this approach is considered effective to be applied in history learning, especially involving historical sites as learning resources.